Clinical Outcomes in Relation to Total Hospital Surgical and Transcatheter Aortic Valve Replacement Volumes - Ayman Elbadawi; Amr Mohamed; Ramy Sedhom; Lisardo Garcia; Ambarish Pandey; Saket Girotra; Anthony Bavry; Sreekanth Vemulapalli; Dharam J. Kumbhani (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background There is a paucity of data regarding the relationship between overall hospital volumes for total aortic valve replacement (AVR; transcatheter AVR [TAVR] or surgical AVR [SAVR]) and patient outcomes. Methods and Results We queried the 2019 Nationwide Readmission Database for patients undergoing AVR. Based on procedural volumes of TAVR or SAVR, we classified hospitals as high (≥50th percentile) or low (<50th percentile) volume centers and categorized hospitals as high TAVR/high SAVR, high TAVR/low SAVR, high SAVR/low TAVR, and low TAVR/low SAVR. Multivariable regression models were employed. The main study outcomes were in‐hospital mortality and 30‐day readmission after total AVR. Our final analysis included 72 123 patients undergoing AVR at 400 hospitals across the United States. The median (interquartile range) hospital procedural volumes for total AVR, TAVR, and SAVR were 137 (86–210), 82 (50–127), and 56 (31–87) procedures, respectively. There was an inverse correlation between hospital procedural volumes of AVR, TAVR, or SAVR and in‐hospital mortality after total AVR but not with 30‐day readmission. Using high TAVR/high SAVR hospitals as reference, there was higher in‐hospital mortality after total AVR among low TAVR/low SAVR hospitals (adjusted odds ratio [OR], 1.29 [95% CI, 1.07–1.56]) but similar in‐hospital mortality among high TAVR/low SAVR hospitals and low TAVR/high SAVR volumes. There was no difference in 30‐day readmission rates after total AVR among the 4 hospital categories. Conclusions Nationwide data revealed that in‐hospital mortality after total AVR (SAVR or TAVR) is inversely related to hospital total volumes of AVR. Patients with aortic stenosis have better outcomes if they are managed among experienced centers with high case volumes of both TAVR and SAVR.